Anterior Cruciate Ligament (ACL) Reconstruction Augmented With Bone Marrow Concentrate, Demineralized Bone Matrix, Autograft Bone, and a Suture Tape (The Fertilized ACL) - Chad Lavender, M.D; Vishavpreet Singh, M.D. (PGY 4); Galen Berdis, M.D. (PGY 4); William Fravel, M.D. (PGY 3); Collin Lamba, M.D. (PGY 2); Tyag Patel, M.D. (PGY 3) (Elsevier, 2021)
Purpose: To examine the early clinical outcomes as well as safety of the Fertilized anterior cruciate ligament (ACL) reconstruction procedure. Methods: A total of 16 consecutive patients with a mean age of 24 years (range, 16-45 years), who had been treated with the fertilized ACL were evaluated and followed over 2 years. Four patients underwent reconstruction using an FGL GRAFTLINK allograft (LifeNet Virginia Beach, VA) and 12 using quadriceps autografts. All patients received the fertilized ACL as previously described using bone marrow composite, demineralized bone matrix, and an internal brace (Arthrex, Largo, FL). Clinical outcomes at 2 years including International Knee Documentation Committee and Marx scores were evaluated. Complication rates, including return to operating room, arthrofibrosis, infection, and rerupture rates, were also assessed. Results: All patients were followed for 6 months and all were released to full activity. In total, 11 of 16 patients were available for 2-year follow-up after the fertilized ACL reconstruction. At 2 years, the average International Knee Documentation Committee and Marx scores were 81 (standard deviation, 5.9) and 9 (standard deviation, 5.7), respectively. One patient required a return trip to the operating room for manipulation under anesthesia. No reruptures were observed at the 2-year mark. Nine of 11 patients had returned to their preinjury activity status at 2 years. Conclusions: The fertilized ACL, which adds biology and an internal brace to an ACL reconstruction, is a reliable and safe option when performing an ACL reconstruction. Very low complication risks were seen in this consecutive series followed for 2 years. Patients consistently returned to their preinjury activity status. Level of Evidence: Level IV, therapeutic case series.